THE IMPACT OF ARTIFICIAL INTELLIGENCE IN IMPROVING NUMBER AND LETTER LITERACY IN EARLY CHILDHOOD - Sit, Masganti; Halimah, Siti; Robingatin, Robingatin; Hasnida, Hasnida; Lita, Lita (International Conference on Humanity Education and Society (ICHES), 2024)
Number and letter literacy skills are very important for early childhood. These two skills help children in successful learning at the next level of education. On the other hand, the development of various artificial intelligence applications in learning numbers and letters can be utilized by teachers to improve both skills. This research aims to analyze the impact of artificial intelligence in developing letter and number literacy in early childhood. This research uses a literature review approach sourced from articles that have been published in reputable international journals that examine the relationship between the use of applications in developing literacy of numbers and letters in early childhood. The results show that various artificial intelligence applications have been used to improve number and letter literacy in early childhood. However, the appropriate use needs to be studied in the future.